Non-competitive cyclic peptides for targeting enzyme–substrate complexes. Issue 20 (1st May 2018) - McAllister, T. E.; Yeh, T.-L.; Abboud, M. I.; Leung, I. K. H.; Hookway, E. S.; King, O. N. F.; Bhushan, B.; Williams, S. T.; Hopkinson, R. J.; Münzel, M.; Loik, N. D.; Chowdhury, R.; et al.
Abstract : Tight, non-active site binding cyclic peptides are promising affinity reagents for studying proteins and their interactions. Abstract : Affinity reagents are of central importance for selectively identifying proteins and investigating their interactions. We report on the development and use of cyclic peptides, identified by mRNA display-based RaPID methodology, that are selective for, and tight binders of, the human hypoxia inducible factor prolyl hydroxylases (PHDs) – enzymes crucial in hypoxia sensing. Biophysical analyses reveal the cyclic peptides to bind in a distinct site, away from the enzyme active site pocket, enabling conservation of substrate binding and catalysis. A biotinylated cyclic peptide captures not only the PHDs, but also their primary substrate hypoxia inducible factor HIF1-α. Our work highlights the potential for tight, non-active site binding cyclic peptides to act as promising affinity reagents for studying protein–protein interactions.